Colliding constructs : exploring discourses regarding traditional marriage and lesbian marriage : a literature review - Padfield, Lisa Rae (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2007.